Dampak inflasi dan Nilai Tukar Uang Bagi Pelunasan Hutang Pada Masyarakat Trebungan Mlandingan Situbondo Perspektif Fiqh Muamalah - Isvina Vawaidatur Rohmah (Jurnal Ilmiah Ekonomi Islam, 2023)
We all know that the currency we use always experiences a decline in exchange rates from time to time. If it is associated with debt transactions, of course this is a problem. Do you still have to pay with the same amount as when borrowing, or with the currency value when paying off after experiencing inflation? This study aims so that people can find out the correct repayment of debt after inflation occurs or not and avoid usury. From the results of the study it can be concluded that inflation and exchange rates do not have a major impact on repayment of debts to the people of Trebungan Mlandingan Situbondo. Although there are some who ask for additional payments to be charged to borrowers due to inflation, the majority of them do not take into account the fluctuations in the exchange rate when paying off debt. So that inflation and fluctuations in the value of money do not affect the time of repayment of debt.